METHOD OF PERFORMING THE TRANSACTIONS ON MEDICAL DATA BASED ON BLOCKCHAIN TECHNOLOGIES - OSYADLYI, Vitaliy; MOSKALENKO, Artem (Herald of Khmelnytskyi National University. Technical sciences, 2022)
Abstract. Today, healthcare decision-making processes are time consuming and complex. The productivity of health workers can be increased through the use of information technology. It is information technology that can reduce medical errors, provide more reliable solutions, and reduce health care costs. Today, medical information technology must meet 4 requirements: efficiency, safety, novelty and economic benefits. The healthcare sector in Ukraine has long been in need of change, and the many opportunities blockchain technology can help it lead the transformation of this area and meet these 4 requirements. Thus, increased attention to the technology of distributed registries has led to an understanding of the potential of blockchain technology in the health care system. Thus, the current challenge is the need to manage medical data based on blockchain technologies. The conducted state-of-the-art on known decisions on the use of blockchain technologies in the construction of information technology for medical data management showed that, despite a large number of different solutions, effective methods and solutions for medical data management based on blockchain technologies are currently lacking. Thus, improving the efficiency of medical data management by developing methods of medical data management based on blockchain technologies is currently an urgent problem. The aim of this study is to increase the efficiency of medical data management by developing a method of performing transactions on medical data based on blockchain technologies. A method of performing the transactions on medical data based on blockchain technologies has been developed, which consists of the stages of entering information into the blockchain and obtaining information from the blockchain. The developed method of performing the transactions on medical data provides: the ability to decide on the addition of transactions and medical data from the patient to the blockchain; the ability to decide on the issuance of data from the blockchain on request from a doctor.